2006
DOI: 10.1002/anie.200503822
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition of a Three‐Way DNA Junction by a Metallosupramolecular Helicate

Abstract: Three point turn: A metallosupramolecular helicate with trigonal‐antiprismatic geometry fits perfectly into the central hydrophobic cavity of a three‐way DNA junction allowing a new mode of DNA recognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
164
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 286 publications
(172 citation statements)
references
References 42 publications
4
164
0
4
Order By: Relevance
“…Oleksi et al (39) have reported the crystallization of a threeway DNA junction around a dinuclear iron(II) supramolecular helicate. Each of the three DNA strands are kinked in the center by some 60°between adjacent Tand A bases, with which the polypyridyl ligands of the complex make stacking interactions, thus opening up a cavity in which to accommodate the tetracationic helicate.…”
Section: Discussionmentioning
confidence: 99%
“…Oleksi et al (39) have reported the crystallization of a threeway DNA junction around a dinuclear iron(II) supramolecular helicate. Each of the three DNA strands are kinked in the center by some 60°between adjacent Tand A bases, with which the polypyridyl ligands of the complex make stacking interactions, thus opening up a cavity in which to accommodate the tetracationic helicate.…”
Section: Discussionmentioning
confidence: 99%
“…电相互作用, 面对面插入型的 π-π 堆积作用, C-H…X 型氢键相互作用和小沟的夹心作用 [65] . 作者还发现 [Fe 2 26 3 ] 4+ 超分子螺旋体可以大量提取质粒 DNA, 比常 规 DNA 浓缩剂更有效, 而且还可以抑制 DNA 相关酶的 活性 [66] .…”
Section: 含硫含氮配体形成的双螺旋unclassified
“…The latter displayed the ability to induce conformational changes in the DNA decamer [d(GACGGCCGTC) 2 ] [5]. Hannon also showed that this triply stranded helicate non-covalently binds at the centre of three-way (Y-shaped) DNA [6][7][8][9] and RNA [10] 4+ helicates have been found to display micromolar cytotoxicity against a range of cancer cell lines [11,12] 4+ helicate has been shown to display modest antibacterial activity against Bacillus subtilis (minimum inhibitory concentration (MIC) = 32 µg·mL −1 ) and Escherichia coli (MIC = 64 µg·mL −1 ) [13].…”
Section: Introductionmentioning
confidence: 99%